Oral patterns of performance: story and song - Toelken, Barre, author; Utah State University Press, publisher (Colorado State University. Libraries, 2014)
To many Native American cultures, songs and stories are dramatic enactments of reality. To some words bring reality into existence. In this chapter from his award-winning The Anguish of Snails, Toelken thoughtfully approaches a number of stories from Native American traditions. He discusses how narratives can be touchstones of shared values among closely associated traditional people and how songs and stories go far beyond an evening's entertainment or "lessons" about life. A traditional narrative can be a culturally structured way of thinking and of experiencing the patterns that make culture real.
Current Arguments in Folklore edition.
Keywords: Indians of North America -- West (U.S.) -- Folklore; Folklore -- Performance -- West (U.S.); Oral tradition -- West (U.S.); Folklore -- Methodology; Folklore -- United States.